2021
DOI: 10.1126/sciadv.abd6734
|View full text |Cite
|
Sign up to set email alerts
|

Efferocytosis fuels malignant pleural effusion through TIMP1

Abstract: Malignant pleural effusion (MPE) results from the capacity of several human cancers to metastasize to the pleural cavity. No effective treatments are currently available, reflecting our insufficient understanding of the basic mechanisms leading to MPE progression. Here, we found that efferocytosis through the receptor tyrosine kinases AXL and MERTK led to the production of interleukin-10 (IL-10) by four distinct pleural cavity macrophage (Mφ) subpopulations characterized by different metabolic states and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…Some signalling pathways including TGF‐β2 could modulate ECM formation in multiple organs, such as the eye, liver and lungs 37–39 . Therefore, TGF‐β2 is used to design fibrosis models in vivo, including glaucoma and liver fibrosis 40–42 . Studies have shown that TGF‐β2 could contribute to ECM deposition and inhibit ECM transformation in the AH or trabecular meshwork of glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some signalling pathways including TGF‐β2 could modulate ECM formation in multiple organs, such as the eye, liver and lungs 37–39 . Therefore, TGF‐β2 is used to design fibrosis models in vivo, including glaucoma and liver fibrosis 40–42 . Studies have shown that TGF‐β2 could contribute to ECM deposition and inhibit ECM transformation in the AH or trabecular meshwork of glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Therefore, TGF-β2 is used to design fibrosis models in vivo, including glaucoma and liver fibrosis. [40][41][42] Studies have…”
Section: Matn2mentioning
confidence: 99%
“…TIMP1 is a secretory glycoprotein that inhibits MMPs, a group of conserved peptidases that degrade ECM proteins 60 . TIMP1 also inhibits cell apoptosis 61 , promotes cell proliferation 62 , and benefits bone health 63 .…”
Section: Discussionmentioning
confidence: 99%
“…TIMP1 augmented macrophage migration and its transformation to M2 type ( 45 ). Reversely, IL10 induces dendritic cells to produce TIMP1 ( 46 ). Furthermore, anti-inflammatory M2-type macrophages down-regulate the expression of VCAM1 in endothelial cells ( 47 ).…”
Section: Discussionmentioning
confidence: 99%